The Effect of the Think Talk Write (TTW) Cooperative Learning Model on Grade 10 Students' Mathematical Creative Thinking Skills at Al-Istiqamah Senior High School, West Pasaman - Rendy B. Suharsono; Armiati Armiati; Khairani Khairani; Yulyanti Harisman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
An important skill in mastering mathematics is the ability to think creatively about mathematical problems. Students in Grade X Phase E at SMA Al-Istiqamah Pasaman still exhibited modest levels of mathematical creativity. The purpose of this research was to describe the growth of students' mathematical creative thinking abilities and to find out whether students taught using the Think Talk Write (TTW) cooperative learning paradigm outperformed those taught using direct teaching. Using a nonequivalent posttest-only control group design, this research utilized a quasi-experimental technique. The students from Class X E 3 and Class X E 8 were used as the experimental and control groups, respectively, in this study of all Grade X Phase E students at SMA Al-Istiqamah Pasaman. A mathematical creative thinking essay test served as the research instrument. A significance value of 0.01 (Sig. 2-tailed < 0.05) was obtained from the data analysis conducted using an independent samples t-test, suggesting a notable distinction between the experimental and control groups. Thus, compared to students who received direct teaching, those who learnt using the Think Talk Write (TTW) cooperative learning paradigm showed greater improvement in mathematics creative thinking.